Finance-dominated capitalism, re-distribution, household debt and financial fragility in a Kaleckian distribution and growth model - Eckhard Hein (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2011)
In a Kaleckian distribution and growth model with workers' debt we examine the short- and long-run effects of three stylized facts of 'finance-dominated capitalism': a fall in animal spirits of the firm sector with respect to real investment in capital stock, re-distribution of income at the expense of the wage share, and increasing lending of rentiers to workers for consumption purposes. In particular, we specify the conditions for long-run stability of the workers' debt-capital ratio. We thus identify the threshold for this ratio to turn unstable causing increasing financial fragility and finally financial crisis due to systemic stock-flow or stock-stock dynamics.
Keywords: E12; E21; E22; E25; O41; 330; Finance-dominated capitalism; distribution; household debt; financial fragility; growth; Kaleckian model